The influence of obstructive sleep apnea and continuous positive airway pressure on the nasal microbiome - Lenk, Christian; Meßbacher, Maria-Elena; Abel, Judith; Müller, Sarina Katrin; Mantsopoulos, Konstantinos; Gostian, Antoniu-Oreste; Sievert, Matti; Wirtz, Stefan; Marxreiter, Franz; Winkler, Jürgen; Iro, Heinrich; Traxdorf, Maximilian (European Review for Medical and Pharmacological Sciences, 2023)
OBJECTIVE: The aim of this study was to investigate the influence of obstructive sleep apnea and continuous positive airway pressure on the nasal microbiome. PATIENTS AND METHODS: Endonasal swabs from the olfactory groove of 22 patients with moderate and severe obstructive sleep apnea (OSA) and a control group of 17 healthy controls were obtained at the Department of Otorhinolaryngology of the Friedrich-Alexander-Universität Erlangen-Nürnberg. 16S rRNA gene sequencing was performed to further evaluate the endonasal microbiome. In a second step, the longitudinal influence of continuous positive airway pressure (CPAP) therapy on the nasal microbiome was investigated (3-6 and 6-9 months). RESULTS: Analysis of the bacterial load and β-diversity showed no significant differences between the groups, although patients with severe OSA showed increased α-diversity compared to the control group, while those with moderate OSA showed decreased α-diversity. The evaluation of longitudinal changes in the nasal microbiota during CPAP treatment showed no significant difference in α- or β-diversity. However, the number of bacteria for which a significant difference between moderate and severe OSA was found in the linear discriminant analysis decreased during CPAP treatment. CONCLUSIONS: Long-term CPAP treatment showed an alignment of the composition of the nasal microbiome in patients with moderate and severe OSA as well as an alignment of biodiversity with that of the healthy control group. This change in the composition of the microbiome could be both part of the therapeutic effect in CPAP therapy and a promoting factor of the adverse side effects of the therapy. Further studies are needed to investigate whether the endonasal microbiome is related to CPAP compliance and whether CPAP compliance can be positively influenced in the future by therapeutic modification of the microbiome.
CRIS-Team WoS Importer:2023-05-26